KOLABORASI STAKEHOLDERS DALAM PEMBERDAYAAN MASYARAKAT (STUDI KASUS DI DESA WONOYOSO, KECAMATAN PRINGAPUS, KABUPATEN SEMARANG) - Rizka Ciptaningsih; Herbasuki Nurcahyanto (Journal of Public Policy and Management Review, 2019)
Community empowerment in Wonoyoso village is constrained by the passivity of the village government. This research aims to see collaboration between stakeholders established in Wonoyoso Village, the impact on the community empowerment, and the influencing factors. This research uses a qualitative method with data collection techniques of observation, interviews, and documentation. Determination of research subjects using purposive sampling technique and convenience sampling. The data validity use triangulation techniques. The results of the study show that the stakeholders that occurred in Wonoyoso Village did not work well. The stakeholders involved are: village government, sub-district government, DISPERMADES, DISKOPUMKMPERINDAG, Education Agency and Health Office in this case represented by the PUSKESMAS. The less active stakeholders are the village government. The positive impacts of the empowerment are: The Increasing of community participation in economic and health activities, the increasing of human resources quality, increased employment opportunities through MSME activities, and the negative impacts are: few PAUD's participants, and jealousy or injustice arising in the community associated with involvement in MUSRENDES. Inhibiting factors: passive village parties, minimal opportunities, no coordinating body; Supporting factors: responding local government, high community participation, organizations that have official permission. Suggestions that can be given are: making commitments between the village and residents, increasing the amount of the budget for community empowerment, and enforcing the DISPERMADES roles as the coordinator.